Globalization as Racialized, Sexualized Violence THE CASE OF INDIGENOUS WOMEN - Kuokkanen, Rauna (International Feminist Journal of Politics, 2008)
In my article, I suggest that indigenous women are among the hardest hit by economic globalization – the expansion of markets, trade liberalization and cheapening of labour – and that globalization represents a multifaceted violence against indigenous women. I consider this with the help of two examples. First, I discuss the largely ignored case of missing and murdered Aboriginal women in Canada and how the interlocking systems of oppression (colonization, patriarchy and capitalism) are further intensified by globalization. Second, I examine the death of a Hopi woman, Private Piestewa, in the context of militarization, history of colonization and globalization. I analyse these examples in an intersectional framework that reveals the links between colonization, patriarchy and capitalism all of which inform the current processes of globalization.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; armée états-unienne; canada; capitalisme; cours; discipline; féminicide; globalisation; histoire et politique; intersectionnalité; militarisation; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis

L'ONU, alliée des femmes ? Une analyse féministe du système des organisations internationales - Falquet, Jules (Multitudes, 2003)
Cet article analyse la stratégie du système onusien pour neutraliser les mouvements sociaux contestataires en les faisant « participer » à son projet de « bonne gouvernance » mondiale, à travers l’exemple du mouvement féministe latino-américain et des Caraïbes. En étudiant les « politiques de population » des institutions internationales et la question du micro-crédit pour les femmes, on voit comment l’ONU parvient à se présenter comme « alliée » des femmes et à embrigader dans son entreprise une partie du mouvement féministe, alors qu’elle applique des politiques désastreuses pour les femmes, en particulier pour les femmes pauvres du Sud.
Keywords: amérique latine; amériques; approches et analyses; capitalisme; caraïbes; cours; discipline; histoire et politique; inégalités; oppressions institutionelles; philosophie; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs -- qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those -- the vast majority -- who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe

Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (Worlds of desire, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis